2008
DOI: 10.1152/ajprenal.00608.2007
|View full text |Cite
|
Sign up to set email alerts
|

Mouse model of type II Bartter's syndrome. I. Upregulation of thiazide-sensitive Na-Cl cotransport activity

Abstract: ROMK-deficient ( Romk−/−) mice exhibit polyuria, natriuresis, and kaliuresis similar to individuals with type II Bartter's form of hyperprostaglandin E syndrome (HPS; antenatal Bartter's syndrome). In the present study, we utilized both metabolic and clearance studies to define the contributions of specific distal nephron segments to the renal salt wasting in these mice. The effects of furosemide, hydrochlorothiazide, and benzamil on urinary Na+ and K+ excretion in both wild-type ( Romk+/+) and Romk−/− mice we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 28 publications
4
35
0
Order By: Relevance
“…The urine volume of GFR, ENa, and EK, as well as FENa and FEK before and after administration of furosemide (30 mg/kg intravenously) was measured. As previously reported, furosemide induced a significant diuretic and natriuretic effect with mild reductions of GFR in the control mice (5). The new observation is that furosemide also produced a significant diuretic and natriuretic effect in Romk1 Ϫ/Ϫ mice.…”
Section: Generation Of Romk1 Knock-out Mice Bysupporting
confidence: 81%
See 1 more Smart Citation
“…The urine volume of GFR, ENa, and EK, as well as FENa and FEK before and after administration of furosemide (30 mg/kg intravenously) was measured. As previously reported, furosemide induced a significant diuretic and natriuretic effect with mild reductions of GFR in the control mice (5). The new observation is that furosemide also produced a significant diuretic and natriuretic effect in Romk1 Ϫ/Ϫ mice.…”
Section: Generation Of Romk1 Knock-out Mice Bysupporting
confidence: 81%
“…By using the Romk Bartter mouse model, we have further confirmed that ROMK forms both small conductance K ϩ channels (SK) and 70 pS K channels in apical membranes of the thick ascending limb and cortical collecting duct (3,4). We have demonstrated: 1) absence of both SK activity and 70 pS K ϩ channels in apical membranes of thick ascending limb and cortical collecting duct in Romk knock-out mice; 2) Romk knock-out mice produced similar phenotypes to Bartter syndrome consisting of salt and water wasting due to reduced NKCC2 activity and expression (3,5); 3) the salt and water wasting from the kidney is compensated by increased thiazide-sensitive NaCl transport expression and activity, distal tubule hypertrophy, elevated renin-Ang II, and aldosterone levels (6). 4) The reduced K ϩ secretion in Romk null mice is compensated by increased maxi-K channel activity in the collecting tubule (7).…”
mentioning
confidence: 89%
“…17 In some cases, structural remodeling correlates with changes in Na + transport function: DCT hypertrophy is associated with increased Na + transport capacity in microperfused distal tubules in rats exposed to chronic furosemide 9,18 and with enhanced thiazidesensitive Na + excretion in a mouse model of Bartter's syndrome. 19 The cause of DCTremodeling is not fully understood; it has been hypothesized that increased luminal Na + delivery stimulates a hypertrophic response dependent on proportional changes in [Na + ] i . 20,21 In the presence of a tonic stimulus to NaCl reabsorption in the DCT, such a mechanism could result in a positive-feedback loop whereby excessive NaCl reabsorption begets epithelial hypertrophy and yet more NaCl reabsorption.…”
Section: Namentioning
confidence: 99%
“…DCT hypertrophy is associated with enhanced NaCl transport in salt-losing states, 9,18,19 contributing to a homeostatic defense against salt and water loss. We found that the increase in pNCC evoked by chronic furosemide was associated with enhanced thiazide-sensitive Na + reabsorption.…”
Section: What Is the Functional Consequence Of Dct Hypertrophy?mentioning
confidence: 99%
“…Thus loss-of-function mutations in the ROMK (Kcnj1) result in HPS (type II Bartter's syndrome). In a companion paper, we characterized the renal phenotype of the ROMK null (Romk Ϫ/Ϫ ) mouse model of type II Bartter's syndrome based on the effects of specific loop of Henle and distal tubule diuretics on renal water and electrolyte excretion (4). Impaired Na ϩ transport in the TAL leads to enhanced downstream Na ϩ delivery to the DCT, connecting tubule (CNT), and cortical collecting duct (CCD) (for a review, see Refs.…”
Section: CLmentioning
confidence: 99%